DECISION SUPPORT SYSTEM TO DETERMINE THE LOCATION NEW CAFE SUNCAFE AS A TOURIST CULINARY TOUR IN DISTRICT PRINGSEWU BY USING SIMPLE ADDITIVE WEIGHTING - Arif Hidayat; Indah Tri Utami (STMIK Pringsewu Lampung, 2017)
District Pringsewu is growing that are doing development of various sectors, one of the tourism sectors. Culinary tourism in the District Pringsewu growing quite rapidly, has a lot of standing places that sell a lot of food choices, from street vendors to modern eating places like cafes. Many cafes in the district of Pringsewu would be a separate issue in determining the appropriate location for the new cafe location Suncafe, for it needed a system that could help determine the location of a new cafe. The criteria used in making this decision support system include building area, spacious parking, accessibility, security, distance to the city center, the price of the location, and comfort. Decision support system is made using a simple additive weighting method (SAW) is looking for a weighted sum of the performance of each alternative. While the implementation of the program for decision support system is made by using Delphi 7. Obtained 3 major end result rankings to determine the locations of a new cafe, there are 1. District Pagelaran with a value of 80, 2 District Gadingrejo with a value of 79, and 3 districts Adiluwih with a value of 78.55.